Clinical and immunopathological assessment of the oral mucosa in coeliac disease: a pilot study - Agnieszka Mania-Końsko; Zuzanna Ślebioda; Aleksandra Dańczak-Pazdrowska; Marzena Liliana Wyganowska (BMC Oral Health)
Abstract Background Coeliac disease (CD) is a lifelong immune-mediated systemic disease that develops in genetically predisposed subjects who show intolerance to gluten proteins. Intestinal wall inflammation with villi atrophy results in malabsorption of nutrients and leads to several gastrointestinal and systemic symptoms. High serum levels of anti-endomysial and anti-tissue transglutaminase autoantibodies can be revealed in patients with CD. The aim of the study was to evaluate the presence of IgA, IgG, IgM, and C3 complement deposits in the oral mucosa and its condition in CD patients. Methods Thirty CD patients underwent complete clinical examination followed by mycologic evaluation, of whom 10 additionally had oral mucosa biopsy. Direct immunofluorescence (DIF) was performed on the oral mucosa specimens using polyclonal rabbit IgG, IgA, IgM, and C3 antibodies. The results were statistically analyzed. Results The most common complaints included pain due to oral ulcers, xerostomia, and gingival bleeding. Frequently observed comorbidities were anemia, allergy, and thyroid disorders. Common oral mucosal findings included white-coated tongue, linea alba, and atrophic glossitis. Candidiasis was revealed in 13 subjects (43.3%). IgA, IgG, IgM, or C3 deposits in the oral mucosa specimens were shown in none of the patients. Conclusions Coeliac disease may increase the frequency of white-coated tongue, linea alba, and atrophic glossitis and may promote the development of oral candidiasis. However, there are no evident markers in the CD patients’ immunopathologic examination of the oral mucosa specimens.